Maternal death by COVID-19 in a reference hospital in Mato Grosso: a descriptive study (Research, Society and Development, 2022)
The study aims to describe the sociodemographic, obstetric and clinical characteristics of women who died as a result of COVID-19 infection during the pregnancy-puerperal cycle, in a referral hospital in Cuiabá, Mato Grosso. This is a descriptive study composed of 8 women, with a mean age of 27.5 years. There was a predominance of mixed-race women, coming from municipalities other than the one of hospitalization. Most of them had no comorbidity or complications before infection, all women had pulmonary alterations and 6 of them suffered fetal involvement. The average length of hospital stay was 12 days and the main causes mentioned in the death certificates were: respiratory failure, viral pneumonia due to COVID-19 infection, septic shock and hypovolemic shock. Women in the gestational period need expanded, rigorous and specific care, and adequate and timely prevention and treatment measures, since COVID-19 infection poses risks not only to the mother, but also to the fetus/newborn.